2010
DOI: 10.1111/j.1755-3768.2010.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

The Eye Amputated – Consequences of Eye Amputation with Emphasis on Clinical Aspects, Phantom Eye Syndrome and Quality of Life

Abstract: . In this thesis the term eye amputation (EA) covers the removing of an eye by: evisceration, enucleation and exenteration. Amputation of an eye is most frequently the end‐stage in a complicated disease, or the primary treatment in trauma and neoplasm. In 2010 the literature is extensive due to knowledge about types of surgery, implants and surgical technique. However, not much is known about the time past surgery. The purpose of the PhD thesis was:  To indentify the number of EA, the causative diagnosis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 138 publications
4
34
1
Order By: Relevance
“…5 Triggers of PES also reflected previous findings, that is, darkness, closing the eyes, and psychological stress. 4,5,8 Although our patients reported that many instances ended spontaneously, patients also could end them by distraction or sleep.…”
Section: Comparison With Published Researchsupporting
confidence: 70%
See 2 more Smart Citations
“…5 Triggers of PES also reflected previous findings, that is, darkness, closing the eyes, and psychological stress. 4,5,8 Although our patients reported that many instances ended spontaneously, patients also could end them by distraction or sleep.…”
Section: Comparison With Published Researchsupporting
confidence: 70%
“…5 Triggers of PES also reflected previous findings, that is, darkness, closing the eyes, and psychological stress. 4,5,8 Although our patients reported that many instances ended spontaneously, patients also could end them by distraction or sleep. Our finding that younger patients were more likely than older ones to report visual sensations and pain concurs with the findings of Sörös et al, 3 but not with those of Rasmussen et al 4 and Rasmussen, 5 who reported that visual sensations were more common in older patients.…”
Section: Comparison With Published Researchsupporting
confidence: 70%
See 1 more Smart Citation
“…Daily cleaning as practiced by patient in Case 2 is not recommended (Osborn and Hetler 2010), because frequent removal may irritate the socket which in turn can cause allergic reaction. Allergic reaction can results in mucus discharge and discomfort to the patient (Hegde et al 2011;Kalavathi et al 2010;Somkuwar et al 2009;Rasmussen 2010). Patient in Case 2 practiced daily removal of ocular prosthesis upon awakening in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have to learn to cope with the loss of binocular vision, with their altered appearance and in those cases where enucleation was performed for a malignancy, patients have to come to terms with the underlying oncological problem. Having cancer or going blind is among the most feared medical conditions, and removal of an eye affects patients in terms of psychological state and quality of life (Rasmussen 2010). When performing an enucleation, it is therefore of utmost importance to choose a surgical procedure and an implant with as few as possible postoperative complications in a quest not to add to the patient's distress.…”
Section: Introductionmentioning
confidence: 99%